Part I: Development of plasma surface modification and characterization strategies for three-dimensional polymer constructs used in biological applications and Part II: Exploring general chemistry students' metacognitive monitoring on examinations - Hawker, Morgan Johanna, author; Fisher, Ellen R., advisor; Rickey, Dawn, committee member; Menoni, Carmen S., committee member; Barisas, George, committee member; Rhodes, Matthew G., committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.
Development of plasma surface modification and characterization strategies for three-dimensional polymer constructs used in biological applications
Exploring general chemistry students' metacognitive monitoring on examinations
Keywords: characterization; plasma; three-dimensional; metacognition; biomedical; polymer